Utilization of geothermal energy resources in rural Alaskan communities. Final report, June 1-December 31, 1974 - Forbes, R.B.; Leonard, L.; Dinkel, D.H. (Alaska Univ., College (USA). Geophysical Inst., 1974)
Three potential geothermal sites in Alaska are discovered. The history of previous use of the hot springs, the socio-economic factors, energy needs, and total energy utilization plans of selected Alaskan thermal springs are presented. Proposed research programs for the sites and environmental hazards and protection are described. (MHR)